2020
DOI: 10.1088/2053-1591/ab727d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed halide contents on structural, electronic, optical and elastic properties of CsSnI3−xBrx for solar cell applications: first-principles study

Abstract: In this study, structural, electronic, optical and elastic properties of CsSnI 3−x Br x perovskites are investigated by full potential linearized augmented plane wave method (FP-LAPW) with exchange correlation functionals GGA-PBE and GGA-mBJ as implemented in Wien2k. The calculated structural parameters for all compositions are in good correlation with literature. The band structures and density of states (DOS) are calculated by GGA which indicated that all these alloys have direct band gap. Furthermore, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Inset of (a) displays the C p / T 3 vs T plot exhibiting a boson-like peak. DFT-calculated (b) bulk modulus and (c) shear modulus of Cs 2 SnI 6 in comparison with other low thermally conductive metal chalcogenides and all-inorganic metal halide perovskites. , …”
Section: Resultsmentioning
confidence: 99%
“…Inset of (a) displays the C p / T 3 vs T plot exhibiting a boson-like peak. DFT-calculated (b) bulk modulus and (c) shear modulus of Cs 2 SnI 6 in comparison with other low thermally conductive metal chalcogenides and all-inorganic metal halide perovskites. , …”
Section: Resultsmentioning
confidence: 99%
“…In a single halide perovskites material, phase stability is calculated by the tolerance equation. 35 where, R A , R B, and R X are represented for the ionic radius of A, B, and I atoms. For stability, the tolerance factor range must be lying in between 0.813 to 1.107.…”
Section: Resultsmentioning
confidence: 99%
“…A quick survey of more than 50 journal articles 22–79 on ABX 3 halide perovskites with mixed compositions ( i.e. , alloying at A, B, and/or X sites) revealed that (a) 66% reported experimental data and 44% reported computational properties; (b) 44% involved A-site mixing, 44% involved B-site mixing, and 52% involved X-site mixing; and (c) a wide variety of properties such as band gaps, effective masses, exciton binding energies, photoluminescence spectra, and photon conversion efficiencies are studied and reported.…”
Section: Introductionmentioning
confidence: 99%